1983
DOI: 10.1007/bf01243369
|View full text |Cite
|
Sign up to set email alerts
|

Regional GABA concentration and [3H]-diazepam binding in rat brain following repeated electroconvulsive shock

Abstract: It has been confirmed that 24 hours following a series of electroconvulsive shocks (ECS) given once daily for 10 days (ECS X 10) to rats there is an increase in GABA concentration in the corpus striatum. A similar change was seen after the ECS had been given to rats anaesthetised with halothane, or when 5 ECS were given spread out over 10 days, the rats being anaesthetised during the ECS. A daily convulsion for 10 days elicited by flurothyl exposure resulted in an increased striatal GABA concentration, but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…Many of the cells lost during chemoconvulsant seizures are GABAergic interneurons (Sloviter, 1987) whereas most of the newly formed cells are excitatory granule cells (Parent et al, 1998), a combination of events that lowers seizure threshold and creates an epileptogenic state. In contrast, ECS increases postictal seizure threshold by enhancing GABAergic tone (Nutt et al, 1981;Bowdler et al, 1983). Both the increased seizure threshold (Perera et al, 2004) and enhanced GABA activity (Sanacora et al, 2003) seen postictally with ECT correlate with positive clinical outcome in depressed patients, which is consistent with our theories that the therapeutic benefits of ECT stem from GABAergic stabilization of mood (Sackeim et al, 1983).…”
Section: Discussionsupporting
confidence: 79%
“…Many of the cells lost during chemoconvulsant seizures are GABAergic interneurons (Sloviter, 1987) whereas most of the newly formed cells are excitatory granule cells (Parent et al, 1998), a combination of events that lowers seizure threshold and creates an epileptogenic state. In contrast, ECS increases postictal seizure threshold by enhancing GABAergic tone (Nutt et al, 1981;Bowdler et al, 1983). Both the increased seizure threshold (Perera et al, 2004) and enhanced GABA activity (Sanacora et al, 2003) seen postictally with ECT correlate with positive clinical outcome in depressed patients, which is consistent with our theories that the therapeutic benefits of ECT stem from GABAergic stabilization of mood (Sackeim et al, 1983).…”
Section: Discussionsupporting
confidence: 79%
“…The results were obtained by use of the technique of gas chromatography-mass spectrometry (mass fragmentography, Bertillson & Costa, 1976); however, methodological strictures including the precursor-product assumptions inherent in measuring turnover by infusion oflabelled precursors (see Bertillson & Costa, 1976) precluded the use of the method in examining turnover in brain areas such as the cortex and hippocampus. A later study by Bowdler et al (1983) confirmed and extended the observations that the GABA concentration changes in various brain regions following repeated ECS, but did not measure 'Author for correspondence; present address: Astra Neuro- The current studies have demonstrated that a single ECS or flurothyl-induced convulsion can induce marked changes in both GABA synthesis (Green et al, 1987a) and release (Green et al, 1987b) in regions of rat brain. An investigation has therefore been made of the effect of repeated seizures on GABA release in regions ofrat brain and on the rate ofGABA synthesis in various brain regions, the latter study being designed to try to confirm and extend an earlier investigation (Green et al, 1978) by use of a different methodology.…”
Section: Introductionsupporting
confidence: 65%
“…130 On the contrary, with repeated ECT, increases in GABA release, GABA concentration, and GABA B biding sites have been reported in rat brain. 173,274,275 These findings suggest that modulation of GABAergic pathways is involved in ECT mechanisms of action.…”
Section: Antipsychoticsmentioning
confidence: 84%